Teori belajar behavoristik: Classical conditioning (Ivan Pavlov) dan operant conditioning (B.F. Skinner) - Navisah, Dewi (Maliki Interdisciplinary Journal, 2024)
Learning has the ability to influence actions, knowledge, and thinking skills acquired through experience. In this context, behavioristic learning theory explains that the learning process involves changes in behavior that can be concretely observed, measured and assessed. These changes are triggered by a stimulus that triggers the formation of responsive relationships in behavior, in accordance with mechanistic principles. In this article, we will explain behavioristic learning theory, especially in the context of classical conditioning by Ivan Pavlov and Operant Conditioning by B.F. Skinner.